THE USE OF DIGITAL RESOURCES TO ENHANCE LITERACY - Magnago, Walaci; Nunes, Paula de Castro (Seven Editora, 2024)
This article investigated the impact of new digital technologies on the literacy process of students with learning difficulties, with the central problem related to the insufficiency of implementation of these technologies and the inequality of access in schools. The overall objective was to analyze the transformative role of digital tools in the educational context, assessing both the challenges and the opportunities they bring. For this, a mixed method was used, involving bibliographic research and analysis of data collected in the field, with graphs that illustrate teachers’ perceptions about the effectiveness of digital technologies in literacy. The most relevant results indicate that, although most teachers recognize the increase in student engagement and motivation with the use of technologies, obstacles remain related to the lack of infrastructure and adequate teacher training, although digital technologies offer significant potential to improve literacy and personalize teaching, their full impact will only be achieved with consistent investments and coordinated actions between schools, governments and society. The contribution of the research lies in the proposal of solutions for a more inclusive teaching, adapted to the individual needs of students, especially those who face greater barriers in the learning process. DOI:https://doi.org/10.56238/sevened2024.037-004